That “darned Dorsiceratus case” (Copepoda, Harpacticoida, Cletodidae T. Scott)—an attempt of a systematic approach, including the description of three new species - Kai Horst George; Lukas Tönjes; Songül Yurtdaş (Zoosystematics and Evolution)
Despite the generally recognised importance of Copepoda Harpacticoida in aquatic ecosystems, our knowledge of that taxon is still very patchy and even marginal with regard to deep-sea representatives. Nonetheless, studies over the past decades have shown that deep-sea Harpacticoida present an almost overwhelming diversity of species. In order to obtain a most realistic assessment of this, taxonomic studies are essential in addition to faunistic ones. They reveal that particularly rare deep-sea groups can be characterised by a large number of different species even from the same location. One such rare group is the taxon Dorsiceratus Drzycimski, a representative of the so-called Ceratonotus group (Cletodidae T. Scott). The five species known to date, namely Dorsiceratus dinah George & Plum, Do. octocornis Drzycimski, Do. triarticulatus Coull, Do. ursulae George, and Do. wilhelminae George & Plum, indicate a worldwide distribution of Dorsiceratus. On the one hand, they are characterised by very similar morphological features. Simultaneously, however, derived characters occur very scattered, making a clear characterisation of both the species and a monophylum Dorsiceratus difficult. The aim of the present morphological comparison is to substantiate a monophylum Dorsiceratus and also to characterise the species known to date. For this purpose, we studied Dorsiceratus specimens collected from various marine areas over the past 26 years. The monophyly of Dorsiceratus can be justified by the following autapomorphies: (1) mandibular palpus without basal seta 1, (2) P2 enp2 with 1 apical seta, (3) P2 exp3 with tube pore, (4) P4 endopod sexually dimorphic. The species can also be characterised by at least one autapomorphy each. Among a total of 57 individuals we studied, we assigned 12 to three new species: Do. andeep sp. nov., Do. denizae sp. nov., and Do. karinae sp. nov., and one male specimen appears to resemble Do. ursulae. However, the remaining 44 individuals could not be morphologically assigned to any of the known or new species. They were provisionally assigned to eight different morphotypes and a heterogeneous morpho-group, which, however, cannot be justified phylogenetically. According to our results, morphological comparison alone is not sufficient for an unambiguous assignment of future findings to Dorsiceratus. It needs to be supplemented by molecular analyses. A diagnostic key to species is provided.